Atomic structure and dynamics of epitaxial 2D crystalline gold on graphene at elevated temperatures - Chen, Q; He, K; Robertson, A; Kirkland, A; Warner, J (American Chemical Society, 2016)
The atomic level dynamics of gold on graphene is studied at temperatures up to 800 °C using an in situ heating holder within an aberration-corrected transmission electron microscope. At this high temperature, individual gold atoms and nanoclusters are mobile across the surface of graphene and attach to defect sites and migrate along the edges of holes in graphene. Gold nanoclusters on clean graphene show crystallinity at temperatures above their predicted melting point for equivalent sized clusters due to strong epitaxial interactions with the underlying graphene lattice. Gold nanoclusters anchored to defect sites in graphene exhibit discrete rotations between fixed orientations while maintaining epitaxial correlations to the graphene. We show that gold nanoclusters can be two-dimensional with monolayer thickness and switch their crystal structure between two different phases. These results have important implications on the use of gold nanoclusters on graphene at elevated temperatures for applications, such as catalysis and plasmonics.